2021
DOI: 10.1007/978-3-030-90238-4_12
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Cost of Using Amazon Mechanical Turk for Research

Abstract: In this study, we investigate the attentiveness exhibited by participants sourced through Amazon Mechanical Turk (MTurk), thereby discovering a significant level of inattentiveness amongst the platform’s top crowd workers (those classified as ‘Master’, with an ‘Approval Rate’ of 98% or more, and a ‘Number of HITS approved’ value of 1,000 or more). A total of 564 individuals from the United States participated in our experiment. They were asked to read a vignette outlining one of four hypothetical technology pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Research suggests that data collected from MTurk are psychometrically reliable (Buhrmester et al., 2011; Holden et al., 2013), MTurk participants are internally motivated (Buhrmester et al., 2011), and interactive experiments run through MTurk can be just as internally valid as those run in the lab or field experiments (Thomas & Clifford, 2017). On the other hand, some studies have raised concerns regarding MTurk participants’ inattentiveness (Chandler et al., 2014; Saravanos et al., 2021) and discrepancy with more nationally representative samples (Stone et al., 2019). In our study, the fact that participants’ overall performance in the prior knowledge test (0.46) and in the geometry test (0.51) was above the chance level (approximately 0.25) suggest that the current participants were reasonably engaged in solving the items.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that data collected from MTurk are psychometrically reliable (Buhrmester et al., 2011; Holden et al., 2013), MTurk participants are internally motivated (Buhrmester et al., 2011), and interactive experiments run through MTurk can be just as internally valid as those run in the lab or field experiments (Thomas & Clifford, 2017). On the other hand, some studies have raised concerns regarding MTurk participants’ inattentiveness (Chandler et al., 2014; Saravanos et al., 2021) and discrepancy with more nationally representative samples (Stone et al., 2019). In our study, the fact that participants’ overall performance in the prior knowledge test (0.46) and in the geometry test (0.51) was above the chance level (approximately 0.25) suggest that the current participants were reasonably engaged in solving the items.…”
Section: Discussionmentioning
confidence: 99%
“…Given the sensitive nature of the topics of the present research, some participants may not have accurately reported on how often they use drugs, have dark personalities, and are prone to masochistic tendencies. Yet, the combination of online (and hence more anonymous) surveys, multiple IMCs, and plausibility checks should have strongly counteracted dishonest responding (Paolacci et al, 2010; Saravanos et al, 2021). Third, to achieve high statistical power, an online survey with a US-based community sample was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited our participants using the Amazon Mechanical Turk crowdsourcing platform, which has been used previously for such studies [40]. To identify an appropriate minimum size for our sample we looked to the "10 times rule method", which is "the most widely used minimum sample size estimation method in PLS-SEM" [41].…”
Section: Data Collectionmentioning
confidence: 99%